Peningkatan Kompetensi Pengelola Rumah Tinggal Mahasiswa Dalam Memberikan Pelayanan Untuk Menjaga Kewibawaan Kampus Unesa 5 - Sarmini, Sarmini; Gamaputra, Gading; Alrianingrum, Septina; Pahlevi, Rahma Shintya; Dzikri, Muhammad Zulfikar (Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2024)
The opening of Unesa Campus 5 in Magetan Regency has an impact on the campus environment, namely the economic impact with the need for housing for students. The high demand for housing has a negative effect on the surrounding community due to the characteristics of students who come from outside the Magetan Regency area, which is different in terms of values and behavior. So as to overcome these problems, the Directorate of Campus Outside the Main Campus provides solutions through community service by making training to increase the competence of student residence managers. The activity was carried out in Maospati District with gradual socialization. The target of the activity is the manager of the residence in Maospati District, totaling 25 people. This socialization will provide an understanding of the rental mechanism both in terms of procedures and documents that are adjusted to the Standard Operating Procedures, as well as the publication of residential houses through electronic media.